Comparison of Hold-Relax Technique and Active Release Technique in Shoulder Impingement Syndrome (International Journal of Physiotherapy, 2021)
Background: One of the common shoulder joint dysfunction is shoulder impingement syndrome, which produces pain in the joint and reduces overhead elevation movement. It represents the third most frequent disease of the musculoskeletal system. The study's objective was to compare the hold-relax technique and active release technique (ART) among people with shoulder impingement syndrome.Methodology: The study design is an experimental study. Patients diagnosed with Shoulder impingement syndrome were selected for this study. The study was conducted at the Outpatient physiotherapy department, ACS Medical College and Hospital, Chennai. A total of 30 subjects with age groups between 40 and 60 years were selected for the study. Simple Random Sampling method used to divide the samples into two equal groups (15) by lottery method. The total duration of the study was four weeks, with four sessions a week. Outcome measures of the study were pain, range of motion, and shoulder function. And measurement tools used were Goniometer, VAS, and SPADI to collect data for this study.Result: The comparative study between group A and group B shows a significant difference in pain effectiveness, external rotation ROM and function with a p-value >0.0001, and no significant difference in the effectiveness of abduction ROM with a p-value >0.1217 among patient with shoulder impingement syndrome.Conclusion: The study concluded that the active release technique is more effective than the hold-relax technique on pain, abduction ROM, external rotation ROM and shoulder function among patients with shoulder impingement syndrome.